Neonatal jaundice: assessing the knowledge and intending practice of clinical medical students of Bingham University Teaching Hospital, Jos Nigeria - Shehu, Maryam; Shehu, Hassan; Onuwe, Adenoyi A. (International Journal of Research in Medical Sciences, 2019)
Background: Neonatal jaundice is one of the major causes of neonatal morbidity and mortality in Nigeria. There is the need therefore to equip our young upcoming doctors about the disease. Aim of this study was to assess the knowledge of clinical medical students of Bingham University Teaching hospital on Neonatal Jaundice (NNJ). Methods: This was a cross-sectional study carried on clinical medical students of Bingham University Teaching Hospital, Jos. Ethical approval was obtained from the Ethical committee of the Hospital. A semi-structured questionnaire was used to obtain data from 400-600L students using convenience sampling method for all those that consented to the study. Results: A total of 181 students were assessed with a M: F ratio of 1:1.2, age ranged of 18-30 years. About 98% of the students got the definition of jaundice correctly. There was no significant correlation between the definition of NNJ with age, sex educational level and tribe of the students. The major source of information was from their lectures and seminars accounting for 80% of sources. The assessment of the knowledge on the cause of NNJ was good with 145(80%) knowing that hematological/hereditary disease is a cause, 4(2.2%) did not know the cause of NNJ. The highest score for danger signs of NNJ was 98(54%) which was high pitch cry. About 60% of the students knew that blue light is the best colour of light for effective phototherapy, while 42(23%) did not know the answer. There was correlation between the intending practice and the educational level of the students p=0.016. Conclusions: The knowledge of some of the causes and the treatment of NNJ among the BHUTH was good and others were poor, therefore, more teachings and exposures need to be done.